Eating disorders - Maj, Mario, 1953- (New York : J. Wiley, 2003)
Anorexia nervosa, bulimia nervosa and binge eating disorder are all associated with significant emotional and relational stress. They can have serious physical complications. Most cases of anorexia and bulimia nervosa remain undiagnosed, and many diagnosed cases are inappropriately treated. It is therefore essential to reduce the gap between research evidence and clinical experience in order to improve diagnosis and treatment of these mental disorders. This latest volume examines the recurrent social and biological problem of eating disorders and provides:Coverage of all aspects of eating disorders, including diagnosis, epidemiology and pharmacological treatmentContributions from internationally acclaimed expertsAn unbiased and reliable reference pointThis title is the sixth volume in the exciting, innovative WPA Series Evidence and Experience in Psychiatry. Written by internationally renowned psychiatrists, this book series provides evidence-based information for psychiatrists, psychologists, mental health nurses and policy makers.
Classification, diagnosis and comorbidities of eating disorders : a review / Katherine A. Halmi -- Epidemiology and cultural aspects of eating disorders : a review / Hans Wijbrand Hoek, Daphne van Hoeken, Melanie A. Katzman -- Physical complications and physiological aberrations in eating disorders : a review / Francesca Brambilla, Palmiero Monteleone -- Pharmacological treatment of eating disorders : a review / Martina de Zwaan, James Roerig -- Psychological interventions for eating disorders : review / G. Terrance Wilson -- Economic and social burden of eating disorders : a review / Scott J. Crow, Carol B. Peterson.
Includes bibliographical references and index.
Print version record.
Keywords: Eating disorders; Feeding and Eating Disorders; Electronic books; Electronic books